Implanting CNT Forest onto Carbon Nanosheets as Multifunctional Hosts for High‐Performance Lithium Metal Batteries. Issue 5 (14th February 2019) - Zhao, Changtai; Wang, Zhao; Tan, Xinyi; Huang, Huawei; Song, Zhongxin; Sun, Yipeng; Cui, Song; Wei, Qianbing; Guo, Wei; Li, Ruying; Yu, Chang; Qiu, Jieshan; et al.
Abstract: Lithium (Li) metal anodes are considered an ideal anode for the next‐generation Li batteries with high energy density. However, some intrinsic problems, such as Li dendrite growth and tremendous volume change, inhibit their practical applications. Here, an unstacked microstructure is tailored by planting an N‐doped carbon nanotube (CNT) forest on the surface of biomass‐derived large‐aspect‐ratio N‐doped carbon sheets (CSs) (CS‐CNT), which can effectively overcome the easy aggregation properties of CSs. As the host material for Li metal anode, the N‐doping and unstacked natures of CS‐CNT offer sufficient Li nucleation sites, large surface area, and space for smooth and uniform Li deposition, effectively preventing the formation of dendritic Li. As a result, the cell with this electrode can keep high and stable Coulombic efficiency of 98.8% for over 2000 h, superior to the pure CSs and Cu foil electrodes. Additionally, the symmetric cell exhibits significantly enhanced cycle life up to 1500 h as well as lowered hysteresis. The present study sheds light on the design of unstacked porous carbon materials and offers an opportunity to develop high efficiency Li metal anode. Abstract : A tailor‐made N‐doped unstacked microstructure is designed and employed as the host material for Li metal anodes, in which the doped N species and unstacked structure offer sufficient nucleation sites, high surface area, and large space for smooth and uniform Li plating without Li dendrites. Thus, the cell can keep high Coulombic efficiency with an average of 98.8% for over 2000 h.